2023
DOI: 10.1002/ijch.202300004
|View full text |Cite
|
Sign up to set email alerts
|

How to Break the Law: trans‐Hydroboration and gem‐Hydroboration of Alkynes

Abstract: Classical hydroboration is the textbook example of an organometallic reaction under rigorous frontier orbital control: a synergetic bonding mode between substrate and reagent evolves into a four‐membered transition state that enforces syn/suprafacial delivery of H−BR2 to the π‐system. This strict stereochemical “law” remained valid for decades, even after the advent of metal‐catalyzed hydroboration. During the last decade, however, numerous possibilities emerged that allow this paradigm to be challenged. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 140 publications
0
2
0
Order By: Relevance
“…These two examples proved that the strict classical anti-Markovnikov hydroboration mode is apparently not unalterable either. 38 Anionic ligands ( L6 , L7 ) may play an important role in promoting unique selectivity. This novel mechanism in these two reactions that breaks traditional hydroboration rules deserves further exploration.…”
Section: Metal-catalyzed Markovnikov-type Selective Hydrofunctionaliz...mentioning
confidence: 99%
“…These two examples proved that the strict classical anti-Markovnikov hydroboration mode is apparently not unalterable either. 38 Anionic ligands ( L6 , L7 ) may play an important role in promoting unique selectivity. This novel mechanism in these two reactions that breaks traditional hydroboration rules deserves further exploration.…”
Section: Metal-catalyzed Markovnikov-type Selective Hydrofunctionaliz...mentioning
confidence: 99%
“… 4 With respect to the hydroboration of internal alkynes, regio- and stereoselectivity would give mixtures of α- and β-addition, cis - and trans -addition products, due to isomerization and other related processes. 5 …”
Section: Introductionmentioning
confidence: 99%
“…In general, classical (catalytic) hydroborations proceed with cis -selectivity via four-membered ring transition states, where the vacant p- or d-orbital interacts with a π-orbital of the alkyne . In contrast, since 2000, trans -selective hydroborations have also been developed with terminal alkynes as well as internal alkynes through three strategies: (i) a transition-metal-mediated process, (ii) a cation/radical-mediated process, , and (iii) a directing group-mediated process (Figure A) . For example, Fürstner reported that [Cp*Ru]-based complexes can achieve trans -hydroboration of internal alkynes .…”
mentioning
confidence: 99%